2020
DOI: 10.1155/2020/1565306
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Property of Grias neuberthii Extract on Human Colon Cancer Cells: A Crucial Role of Autophagy

Abstract: Traditional herbal medicine has become an important alternative in the treatment of various cancer types, including colon cancer, which represents one of the main health problems around the world. Therefore, the search for new therapies to counteract this disease is very active. Grias neuberthii is an endemic plant located in the Ecuadorian Amazon region, which has been used in traditional medicine for its pharmacological properties, including its ability to inhibit tumor cell growth, although scientific studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…It is very well known that some of the most used drugs in cancer chemotherapy derive from natural products. In this context, the high antiproliferative effects shown by the extracts of some plants, such as Annona montana [15] and Grias neuberthii [72], against several human tumor cell lines are of great interest. Isolated compounds with potent in vitro cytotoxic properties include the flavonoid tricin (52) from Huperzia spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is very well known that some of the most used drugs in cancer chemotherapy derive from natural products. In this context, the high antiproliferative effects shown by the extracts of some plants, such as Annona montana [15] and Grias neuberthii [72], against several human tumor cell lines are of great interest. Isolated compounds with potent in vitro cytotoxic properties include the flavonoid tricin (52) from Huperzia spp.…”
Section: Discussionmentioning
confidence: 99%
“…No evidence for apoptotic markers was recorded; nevertheless, both cell lines showed signs of autophagy after the treatment, including increased Beclin-1 and LC3-II and decreased p62. Lupeol (37), 3 -O-methyl ellagic acid 4-O-β-D-rhamnopyranoside (38), and 19-α-hydroxyasiatic acid 27-O-β-D-glucopyranoside (39) (Figure 7) were identified as the compounds that were likely responsible for the activity [72]. Five quercetin glycosides and one kaempferol glycoside were isolated from hydroalcoholic extracts of leaves and flowers.…”
Section: Macbr Pitón In Pastaza Provincementioning
confidence: 99%
See 1 more Smart Citation
“…Punicalagin (1-30 µg/mL) increased LC3 II cleavage and the formation of autophagosomes in human U87MG glioma cells, by the activation of AMPK and p27 [240]. Recently, it was also shown that Grias nuberthii extract (20-50 µg/mL), which contains lupeol, 3 -O-methyl ellagic acid 4-O-β-D-rhamnopyranoside, and 19-α-hydroxy-asiatic acid monoglucoside, inhibited the growth of human colon cancer (RKO and SW613-B3) cells by inducing autophagy only (increase in Beclin 1, LC3 II and decrease in p62) [241]. It was also reported that ellagic acid (10-100 µM) inhibited the growth of human ovarian cancer cells (ES-2 and PA-1) by blocking the cell cycle at the G1 phase and by inducing apoptosis.…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…Colon cancer (HT-29) positions third as far as frequency, yet second as far as mortality and its expanding in Central and South America because of a continuous progress towards more elevated levels of human turn of events [2]. Colon cancer is the second most common cancer in females and also third in males [3].…”
Section: Introductionmentioning
confidence: 99%